Polynomial-time computing over quadratic maps I : sampling in real algebraic sets - Grigoriev, Dima. (2011)
Given a quadratic map Q : Kn → Kk defined over a computable subring D of a real closed field K, and p ∈ D[Y1,..., Yk] of degree d we consider the zero set Z = Z(p(Q(X)),Kn) ⊆ Kn of p(Q(X1,..., Xn)) ∈ D[X1,..., Xn]. We present a procedure that com¬putes, in (dn)O(k) arithmetic operations in D, a set S of (real univariate representations of) sampling points in Kn that intersects nontrivially each connected component of Z. As soon as k = o(n), this is faster than the standard methods that all have exponential dependence on n in the complexity. In particular, our procedure is polynomial-time for constant k. In contrast, the best previously known procedure is only capable of deciding in nO(k2) operations the nonemptiness (rather than constructing sampling points) of the set Z in the case of p(Y ) = Σi Y i2 and homogeneous Q.